2015
DOI: 10.5897/jahr2015.0310
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of diabetes mellitus in human immunodeficiency virus seropositive subjects co-infected with mycobacterium tuberculosis

Abstract: Diabetes mellitus (DM), mycobacterium tuberculosis (TB) and human immunodeficiency virus (HIV) are important health issues. A bi-directional association between them has been demonstrated by many researchers. The link of DM and TB/HIV is more prominent in developing countries where TB and HIV are endemic and the burden of diabetes mellitus is increasing. A total of 845 subjects were recruited for this study. Fasting blood sugar was determined by the glucose oxidase method while HIV serology was performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In developed countries with low TB and HIV burden, the compliance of HIV services in implementing LTBI screening was often inadequate. The LTBI screening rates among HIV-infected patients in United Kingdom, United States, New Zealand and Italy was 35%, 32%, 55% and 65% respectively (Ogbonnaya et al, 2015;White et al, 2017;Adams et al, 2017;Goletti et al, 2020). A study done by Goletti et al demonstrated that LTBI tests were inconsistently performed and were done more frequently on foreign-born patients, older individuals and those with low CD4 cell count (Goletti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries with low TB and HIV burden, the compliance of HIV services in implementing LTBI screening was often inadequate. The LTBI screening rates among HIV-infected patients in United Kingdom, United States, New Zealand and Italy was 35%, 32%, 55% and 65% respectively (Ogbonnaya et al, 2015;White et al, 2017;Adams et al, 2017;Goletti et al, 2020). A study done by Goletti et al demonstrated that LTBI tests were inconsistently performed and were done more frequently on foreign-born patients, older individuals and those with low CD4 cell count (Goletti et al, 2020).…”
Section: Discussionmentioning
confidence: 99%